2022
DOI: 10.1097/yco.0000000000000830
|View full text |Cite
|
Sign up to set email alerts
|

Green spaces for mental disorders

Abstract: Purpose of reviewMental illness is a global challenge, exacerbated by the coronavirus pandemic. Research suggests access to local green spaces is associated with better mental health, yet access is not always equitable. Evaluation of how nature-based interventions protect and support mental health is therefore required. Recent findingsAccessible local green spaces are associated with better mental health. They encourage active behaviours and social interaction, reduce loneliness and stress. Green views from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The percentage of green space in residential ward was not significantly associated with scores on any of the mental health outcomes after controlling for age and gender. Previous research has demonstrated that both exposure and access to green space is beneficial for mental health outcomes [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. These contrasting findings could be a result of the variety of measures of green space ‘exposure’ utilised in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of green space in residential ward was not significantly associated with scores on any of the mental health outcomes after controlling for age and gender. Previous research has demonstrated that both exposure and access to green space is beneficial for mental health outcomes [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. These contrasting findings could be a result of the variety of measures of green space ‘exposure’ utilised in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…It also includes other natural areas, such as woodlands, forests, and wilderness areas. Evidence suggests that green space close to the home, including urban green space, is associated with a reduced risk of developing anxiety and depression, more positive emotions, greater life satisfaction and reduced loneliness [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Factors proposed to mediate the relationship between green space and mental well-being include air quality and opportunities for physical activity; however, evidence about the factors mediating the relationship between green space and mental illness are less clear [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…How can these skills be transferred and scaled up to community level? What are the ecological aspects of depression (and mental disorders in general) the effect of a person’s disconnection from nature, and how can the natural environment and access to green spaces contribute to prevention and treatment ( 85–87 )? Recent reviews focus on how spirituality, a fundamental human dimension, relates to the pathology of depression and how spirituality may or may not be protective ( 88 , 89 )?…”
Section: Unanswered Questions and Future Dilemmasmentioning
confidence: 99%